Analysis of Dispute over Authority to Conduct Journalist Competency Tests Following Constitutional Court’s Decision No. 38/PUU/XIX/2021 - Yusuf Muhamad Said; Rajab Ritonga (Ikatan Sarjana Komunikasi Indonesia, 2024)
This study discusses a dispute between the Press Council (DP) and the National Board for Profession Certification (BNSP) over the authority to conduct journalist competency tests (UKW) using Hans Kelsen’s and Hans Kaviasky’s Theory of Hierarchy of Law. This research was conducted through a qualitative approach using a normative judicial method in analyzing the Constitutional Court’s Decision No.38/PPU-XIX/2021 concerning the authority to conduct journalist competency tests. Secondary data of this research was obtained through literature and document studies. This research found that there has been no final clarification on the settlement of the legal dispute between DP and BNSP over the authority to conduct journalist competency tests following the Constitutional Court’s Decision No. 38/PPU-XIX/2021 rejecting in full the applicants’ plea. The legal implication of the decision is that both DP and BNSP can continue to conduct journalist competency tests respectively.